A novel robust reset controller implemented through field programmable gate array for oxygen ratio regulation of proton exchange membrane fuel cell. (April 2022) - Linli, Wu; Zhangyi, Shen; Mousavi, Hassan; Gu, Hai
Abstract: This paper considers the nonlinear proton exchange membrane fuel cell model to precisely describe the system dynamics and presents a robust reset control method for regulating oxygen rate and optimizing the operation of the fuel cell system during fast load variations. The proposed reset law eliminates overshoot, shortens settling time, and thus improves the behavior of the closed-loop system, while achieving these goals is impossible by any linear controller. Due to the ability of field programmable gate array (FPGA) in providing high speed and efficient processing through software as well as near-real-time performance verification, the proposed control method is implemented through FPGA to confirm operational capability and high speed flexibility of controller. The results of the implementation of the proposed method and comparison with the hybrid fuzzy proportional integral derivative method exhibit smooth dynamic response, error reduction in terms of various criteria and better capability in tracking the desired oxygen rate despite the drastic changes in load current.